The subcellular localization of the G-protein Gi alpha in the basal ganglia reveals its potential role in both signal transduction and vesicle trafficking - Aronin, N (J Neurosci, 1992)
The G-protein Gi is known to mediate signal transduction in cells by coupling its 41 kDa alpha-subunit to plasma membrane-bound receptors and inhibiting adenylyl cyclase or affecting ion channel function. Although this G-protein has been functionally associated with D2/dopamine and mu-opioid receptors in striatal membranes, its localization to neurons of the neostriatum, a brain region rich in adenylyl cyclase activity, has not been established. Light and electron microscopic study of the basal ganglia was conducted using the immunoperoxidase method and an antiserum directed against the alpha- subunit of Gi. In the neostriatum, immunoreactivity was localized to medium-sized spiny and aspiny neurons and axon terminals that formed symmetric synapses. Some astrocytes and glial processes that encapsulated axospinous complexes were also labeled. Immunoreactive axon terminals were numerous in the globus pallidus and substantia nigra, where they exhibited a dense pattern of distribution characteristic of neostriatal spiny projection neurons. Gi alpha immunoreactivity was distributed to multiple subcellular compartments. In neostriatal somata and dendrites, labeling was present intermittently along plasma membranes, and on rough and smooth endoplasmic reticulum and microtubules. In axon terminals, reaction product appeared on plasma membranes and heavily labeled the membranes of synaptic vesicles. The presence of Gi alpha in axon terminals was confirmed in purified synaptosome preparations. G-proteins consistent with the masses of Go alpha and Gi alpha, respectively, were ADP- ribosylated in the presence of pertussis toxin in striatal synaptosomes. Western blot analysis in purified synaptosome preparations of the neostriatum, globus pallidus, and substantia nigra with the same antiserum used in the immunohistochemistry demonstrated a predominant 41 kDa protein corresponding to the molecular mass of Gi alpha. Immunohistochemical localization of Gi alpha with the immunogold method in a crude striatal synaptosome preparation showed gold particles associated with synaptic vesicles and plasma membranes. Results provide the first direct evidence that Gi alpha is localized to medium-sized neostriatal projection neurons and interneurons, where it is likely to function in membrane-bound signal transduction at the postsynaptic and presynaptic level. The presence of Gi alpha in synaptic vesicle membranes points to another potentially important role for this G-protein in vesicle trafficking, such as that recently shown for smaller-molecular-mass G-proteins.